Spring Integration essentials : integrate the heterogeneous endpoints of enterprise applications with Spring Integration for effective communication - Pandey, Chandan (Community experience distilled., 2015)
This book is intended for developers who are either already involved with enterprise integration or planning to venture into the domain. Basic knowledge of Java and Spring is expected. For newer users, this book can be used to understand an integration scenario, what the challenges are, and how Spring Integration can be used to solve it. Prior experience of Spring Integration is not expected as this book will walk you through all the code examples.